Mechanistic insights into Circ-MBOAT2-mediated regulation of TLK1 through miR-664b-3p in non-small cell lung cancer - DanTing Zhao; Cong Wang; GuangCheng Zhang; ZhengChang Song; ChunYu Luan (Hereditas)
Abstract Background Emerging evidence highlights the critical involvement of dysregulated circular RNAs (circRNAs) in non-small cell lung cancer (NSCLC) pathogenesis. Nevertheless, the precise functional role and mechanistic contributions of circ-MBOAT2 in NSCLC remain poorly characterized. The purpose of this study was to investigate the pathogenesis of NSCLC based on circ-MBOAT2. Methods Our investigation focused on the interplay among circ-MBOAT2, miR-664b-3p, and Tousled-like kinase 1 (TLK1) mRNA in NSCLC tissues, along with their association with the clinical and pathological characteristics of NSCLC patients. Sequences or plasmids were transfected into A549 cells. Gene expressions were identified using RT-qPCR and Western blot analysis. NSCLC cells’ cancerous characteristics were identified using CCK-8, EdU, AnnexinV-PI double staining, and Transwell, while their in vivo growth was assessed through a xenografted tumor assay. To monitor alterations in the CD8+ T cell ratio and inflammatory factors in PBMCs, co-cultures were created with both normal human PBMCs and A549 cells. Evaluations using bioinformatics software, dual luciferase reporter tests, and RIP assays were performed to verify the connection between circ-MBOAT2 and miR-664b-3p, as well as the interaction between miR-664b-3p and TLK1. Results Circ-MBOAT2 expression was up-regulated in NSCLC, and reducing circ-MBOAT2 hampered NSCLC cell proliferation, EMT, immune escape, and tumor growth in vivo. There was a negative correlation between miR-664b-3p expression and circ-MBOAT2, and miR-664b-3p could compete with circ-MBOAT2 for binding. miR-664b-3p downregulation impaired the anti-tumor effect of circ-MBOAT2 reduction on NSCLC cells. TLK1 expression was elevated in NSCLC specimens compared to adjacent normal tissues (p < 0.001), negatively correlated with miR-664b-3p (r=-0.351, p < 0.001), and positively correlated with circ-MBOAT2 (r = 0.341, p < 0.001). In vitro functional experiments showed that silencing TLK1 restrained NSCLC cell proliferation, EMT, and immune escape, whlie TLK1 overexpression rescued the inhibitory effects of miR-664b-3p on NSCLC cell malignant behaviors. Conclusion Circ-MBOAT2 promotes NSCLC cell proliferation, EMT and immune escape by competitively binding to miR-664b-3p to promote TLK1 expression.